2022
DOI: 10.1021/acs.jpcb.2c04230
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Molecular Mechanisms of EGCG and Apigenin on Disrupting Amyloid-Beta Protofibrils Based on Molecular Dynamics Simulations

Abstract: The fibrillization and deposition of amyloid-beta (Aβ) protofibrils are one of the important factors leading to Alzheimer's disease. Molecular dynamics simulations can offer information on intermolecular interaction mechanisms between Aβ protofibrils and Aβ fibrillization inhibitors. Here, in this work, we explore the early molecular mechanisms of (−)-epigallocatechin-3gallate (EGCG) and apigenin on disrupting Aβ42 protofibrils based on molecular simulations. The binding modes of EGCG and apigenin with the Aβ4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Due to the small size of apigenin, it enters into the cavity of Aβ protofibrils, and their association is dominated by electrostatic interactions. On the other hand, hydrophobic interactions play a major role in EGCG-Aβ binding . Apigenin is also an effective inhibitor of α-syn aggregation and inhibits hIAPP fibril formation. , Biflavonoids with double apigenin structures (amentoflavone and bilobetin) display better inhibitory ability against hIAPP aggregation .…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small size of apigenin, it enters into the cavity of Aβ protofibrils, and their association is dominated by electrostatic interactions. On the other hand, hydrophobic interactions play a major role in EGCG-Aβ binding . Apigenin is also an effective inhibitor of α-syn aggregation and inhibits hIAPP fibril formation. , Biflavonoids with double apigenin structures (amentoflavone and bilobetin) display better inhibitory ability against hIAPP aggregation .…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
“…On the other hand, hydrophobic interactions play a major role in EGCG-Aβ binding. 35 Apigenin is also an effective inhibitor of α-syn aggregation and inhibits hIAPP fibril formation. 36,37 Biflavonoids with double apigenin structures (amentoflavone and bilobetin) display better inhibitory ability against hIAPP aggregation.…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
“…ChemDraw Ultra 16.0 34 was used to create the 2D structure of HT (Figure 1b), which was optimized by Gaussian09 utilizing the Hartree−Fock (HF) theory and a 6-31G(d) basis set. 35 To cover the whole α-Syn trimer, a grid box with dimensions of 126 × 126 × 126 Å 3 was used. For molecular docking, the default settings were assigned and the final result was determined to be the pose with the lowest binding energy.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…As an orthogonal Greek-key-like structure, α-Syn trimer is made up of 63 amino acids having residues 37–99 in each chain. ChemDraw Ultra 16.0 was used to create the 2D structure of HT (Figure b), which was optimized by Gaussian09 utilizing the Hartree–Fock (HF) theory and a 6-31G­(d) basis set . To cover the whole α-Syn trimer, a grid box with dimensions of 126 × 126 × 126 Å 3 was used.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, due to available experimental technologies, it is still challenging to systematically visualize the structure and self-assembly process of Aβ42 peptides under various conditions. Molecular simulations, on the contrary, may offer some useful information from the microscopic view, which have been extensively employed in this field. For example, Fatafta et al performed microsecond-scale molecular dynamics (MD) simulations to explore the dynamic behavior of the Aβ42 dimer in different environments and found that the secondary structure of the Aβ42 dimer exhibited a transition from a random coil to a β-sheet in solution, but it was inhibited to some extent in the presence of lipid bilayers. Man et al reported an all-atom MD simulation study on Aβ42 dimers, trimers, and tetramers.…”
Section: Introductionmentioning
confidence: 99%